Manfaat pemberian gabungan selenium dan probiotik pada pengobatan konstipasi fungsional pada anak - Wahyu Ningsih Lestari; Atan Baas Sinuhaji; Supriatmo dr (Fakultas Kedokteran USU, 2012)
Constipation is a common health problem in children and can cause serious problems. The prevalence of constipation in childrenvaries from 0.7% to 29.6% and most of constipation in children (> 90%) is functional in the absence of organic abnormalities.Probiotics are living microorganisms when administered in sufficient quantities will benefit the host. Probiotic bacteria in thegut can increase intestinal motility, improve stool consistency and increase the frequency of defecation so effective in thetreatment of constipation. Selenium is an essential micronutrient required by the majority of the body's organ systems to functionproperly. Oxidative stress thought to be involved as one of the factors causing constipation. Selenium as an antioxidant cantreat functional constipation in children, because the main function of selenium is a cofactor of glutathione peroxidase, whichprotects membranes from oxidative damage.Keywords : functional constipation; selenium; probiotic